The effect of low-dose marine n-3 fatty acids on the biosynthesis of pro-inflammatory 5-lipoxygenase pathway metabolites in overweight subjects: A randomized controlled trial - Nielsen, M.S.; Gammelmark, A.; Madsen, T.; Obel, T.; Aardestrup, I.; Schmidt, E.B. (Prostaglandins, leukotrienes and essential fatty acids, 2012)
Marine n-3 polyunsaturated fatty acids (PUFA) have a variety of anti-inflammatory properties. This study evaluated the effect of n-3 PUFA in a low, but recommended cardioprotective dosage on the formation of 5-lipoxygenase pathway metabolites in overweight subjects. Fifty subjects were randomized to 1.1g of n-3 PUFA or olive oil for 6 weeks. Leukotriene B4 formation decreased by 14% in the n-3 PUFA group which proved to be significant within the group (p=0.005) but not between groups (p=0.25). The formation of 5-hydroxyeicosatetraenoic acid (5-HETE) did not differ significantly between the groups. In the n-3 PUFA group, both 5-hydroxyeicosapentaenoic (5-HEPE) acid and leukotriene B5 increased significantly compared to the control group (p<0.001). In conclusion, we did not observe any significant net anti-inflammatory effect on the 5-lipoxygenase pathway from a daily supplement of 1.1g marine n-3 PUFA for 6 weeks.